Recurrent apical prolapse after high uterosacral ligament suspension - in a heterogenous cohort characterised by a high prevalence of previous pelvic operations - Katrine Dahl Pedersen; Marie Højriis Storkholm; Karl Møller Bek; Marianne Glavind-Kristensen; Susanne Greisen (BMC, 2019)
Abstract Background The apical prolapse is probably the most complex form of pelvic organ prolapse (POP). Adequate apical support is essential in the treatment of POP, as it contributes to the support in all vaginal compartments. This study aimed to evaluate the rate of symptomatic recurrent apical prolapse after high uterosacral ligament suspension (HUSLS), in a cohort of women characterised by a high prevalence of previous pelvic operations and a significant degree of prolapse. Methods This is a retrospective chart review of 95 women who underwent HUSLS for symptomatic apical prolapse from 2002 to 2009 at Aarhus University Hospital, Denmark. Of these women, 97% attended a six-month clinical control. Recurrence was defined as symptomatic vaginal vault prolapse stage 2 or more (according to the International Continence Society (ICS) quantification system). Medical charts were reviewed for a mean period of 7.2 years. Any new contacts due to prolapse were noted. Results Before the operation, 73% of the women were hysterectomised, and 52% had previous prolapse surgery. Stage 2 apical prolapse was reported in 71% of the women, whereas 26% had stage 3 or 4. At six-month follow-up, 19% of the women had recurrent symptomatic apical prolapse, and 9% of the women had symptomatic recurrent prolapse in other compartments 6 months after operation. In all, 35% of the women had a renewed prolapse operation during the long-term follow-up period. Perioperative adverse events were seen in 7%. Two women were re-operated due to postoperative complications. Conclusions This retrospective study of 95 women with a significant degree of prolapse and a high prevalence of previous pelvic operations demonstrates that the rate of recurrent prolapse associated with HUSLS might be higher than originally described. In conclusion, HUSLS may not be the optimal first choice of operation in this group of patients.